Botrytis cinerea (Helotiales Sclerotiniaceae)-induced changes in Vitis vinifera (Vitales Vitaceae) leaves influence the oviposition behaviour and life history of Epiphyas postvittana (Lepidoptera Tortricidae). Issue 6 (2nd November 2017) - Rizvi, Syed; Raman, Anantanarayanan
Abstract : Insects use sensory cues to select plants for feeding and oviposition. For a better offspring survival and life-history performance, the oviposition-site selection by gravid females usually corresponds with plant suitability for the best offspring development. To test this, we used the three-component interacting system involving Botrytis cinerea, a pathogenic fungus on Vitis vinifera, and the plant-feeding Epiphyas postvittana . We hypothesised that the gravid females of E. postvittana discriminate between B. cinerea -infected and uninfected leaves of V. vinifera for oviposition to maximise their offspring performance. We characterised volatiles from B. cinerea -infected and uninfected leaves of V. vinifera . We tested the effect of volatiles from B. cinerea -infected leaves on the olfactory behaviour of E. postvittana using a wind-tunnel assay. We raised the neonate larvae of E. postvittana on B. cinerea -infected and uninfected leaves to characterise their development and life-history performance. The key volatiles from B. cinerea- infected V. vinifera leaves were 2–hexene–1–ol, 2–hexenal (E), 1–hexanol, 3–octanone, and 1–octen–3–ol, whereas the same leaves included highly reduced levels of nonanal, benzaldehyde, acetic acid, and hexanal. Results from the wind-tunnel assays showed that gravid females avoid infected leaves, suggesting that the induced and reduced volatiles, subsequent to infection, may be used as a signal in oviposition-site selection by E. postvittana . This is further confirmed by the total failure of our attempts to rear neonate larvae to adult on B. cinerea -infected leaves.